Life is Too Short to Be Serious All the Time: Donald Duck Presents Unconventional Motivations for Publishing in Academia - Donald, William E.; Duck, Nicholas J. (GILE Journal of Skills Development, 2024)
In this food for thought article, we introduce the ‘Donald Duck Phenomenon’ to consider ten of the more unconventional reasons for publishing in academia. These include (i) symbolic immortality, (ii) personal satisfaction, (iii) a sense of pride, (iv) serious leisure, (v) cause credibility, (vi) altruism, (vii) collaboration with a friend or family member, (viii) collaboration with a hero, (ix) conflict or revenge, and (x) for amusement. The article was inspired by the lead author’s social media search for a co-author with the surname ‘Duck’. Through LinkedIn, the lead author, Associate Professor William E. Donald, who is based in the UK and specialises in Sustainable Careers and Human Resource Management, found a collaborator, Dr Nicholas Duck, who is based in Australia and specialises in Organisational Psychology. While the collaboration may appear to be somewhat ‘quackers’, per one of Donald Duck’s famous phrases “Life is too short to be serious all the time, so if you can’t laugh at yourself then call me… I’ll laugh at you, for you”. We hope that this article offers some interesting insights and acts as a way to stimulate conversation around unconventional reasons for publishing in academia.